African Aquaculture: Genetic Resource and Traditional Knowledge Access and Benefit Sharing Measures. Issue 2 (3rd April 2023) - Humphries, Fran; Lawson, Charles; Benzie, John A. H.; Morrison, Clare
Abstract: Genetic resources are the building blocks for aquaculture breeding programs, biotechnology and conservation. The Convention on Biological Diversity and the Nagoya Protocol are international frameworks for access and benefit sharing (ABS) concerning: (a) the collection and use of genetic resources and associated traditional knowledge; and (b) sharing the benefits of their use with the provider. ABS laws in African countries increasingly apply to resources and knowledge used throughout the production chain for aquaculture, including genes and gene sequences. This paper reviews ABS legislation and peer-reviewed publications in Kenya, Malawi, Tanzania, Uganda and Zambia (leading aquaculture countries with ABS laws) to identify key knowledge gaps for ABS and aquaculture. Using a systematic quantitative literature review method and a qualitative analysis, the main findings are that despite established ABS laws in many of the reviewed countries, there are no analyses on the positive or negative effects of these laws for the conservation, sustainable use of genetic resources, digital sequence information and traditional knowledge relevant to aquaculture and the equitable sharing of benefits from their use. These knowledge gaps may significantly undermine the sharing of resources and knowledge necessary for ecologically sustainable aquaculture development in Africa, which is crucial to food security and livelihoods.